Analysis of Farmers' Behavior Improving Environmental Quality and Some Influencing Factors in the Bantimurung Irrigation Area, Maros District - Samad, Putri IS.; Wahrini, Retyana; A., Ganggang Canggi (MultiTech Publisher, 2024)
Bantimurung District, with a rice harvest area of 10,652 hectares, has an important role in Maros Regency. This research identified a number of main issues, such as farmers' behavior in efforts to improve environmental quality in the Bantimurung irrigation area, knowledge about wet agricultural ecosystems, attitudes towards irrigation, and motivation to protect the environment. This research aims to understand farmers' actions in increasing agricultural production and the environment in a sustainable way, and to measure the impact of various factors, both individually and as a whole. This research method is quantitative using a correlational approach.The research location was chosen using a purposive sampling method in the Bantimurung irrigation area, Maros Regency. The research results show that farmers' behavior in improving environmental quality in the Bantimurung irrigation area has so far only reached a moderate level. Community knowledge about wet agricultural ecosystems, the environment, attitudes towards irrigation, and motivation to protect the environment in these areas tend to be low